Model Konduktivitas Termal Nanofluida Berdasarkan Grup Tak-Berdimensi dengan Parameter Termofisika Kompleks - Yuant Tiandho; Fitri Afriani (Jurnal Fisika FLUX, 2020)
This article presents a model of thermal conductivity of nanofluids based on dimensionless-group methods. In addition to the thermal conductivity of base fluids and nanoparticles, nanoparticle diameter, temperature, and volume fraction of nanoparticles, the proposed model involves several thermophysical parameters such as specific heat, density, and viscosity. The reason for the development of the model requires complex thermophysical parameters because, based on the experiments, these parameters determine the thermal conductivity of nanofluids. Validation of the model through comparison of the model with the experimental results shows that the models that have non-linear correlation have good accuracy in predicting the thermal conductivity of nanofluids.